2007
DOI: 10.1109/twc.2007.05356
|View full text |Cite
|
Sign up to set email alerts
|

MEERA: cross-layer methodology for energy efficient resource allocation in wireless networks

Abstract: Part of the Electrical and Computer Engineering CommonsSuggested Citation: Pollin, S.; Mangharam, R.; Bougard, B.; Van der Perre, L.; Moerman, I.; Rajkumar, R.; Catthoor, F.; , "MEERA: Cross-Layer Methodology for Energy Efficient Resource Allocation in Wireless Networks," Wireless Communications, IEEE Transactions on , vol.7, no.1, pp.98-109, Jan. 2008. ©2008 IEEE. Personal use of this material is permitted. However, permission to reprint/republish this material for advertising or promotional purposes or fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…However, the point-to-point streaming-system under consideration in [1] that only considers a physical layer, the corresponding traffic pattern, and the associated tuning knobs has little in common with today's omnipresent short-range wireless networks (e.g., IEEE 802.11n or IEEE 802.11ac). Based on this observation recent works have been focusing on providing strategies to improve energy-efficiency at the medium-access-control (MAC) layer [27,36]. The latest studies on the component level consider different algorithm choices under the aspect of energy-efficiency, spanning both the algorithm and the architectural layer [15].…”
Section: State Of the Artmentioning
confidence: 99%
“…However, the point-to-point streaming-system under consideration in [1] that only considers a physical layer, the corresponding traffic pattern, and the associated tuning knobs has little in common with today's omnipresent short-range wireless networks (e.g., IEEE 802.11n or IEEE 802.11ac). Based on this observation recent works have been focusing on providing strategies to improve energy-efficiency at the medium-access-control (MAC) layer [27,36]. The latest studies on the component level consider different algorithm choices under the aspect of energy-efficiency, spanning both the algorithm and the architectural layer [15].…”
Section: State Of the Artmentioning
confidence: 99%
“…In [24,25], we showed that a cross-layer combination of both approaches can significantly decrease the energy consumption in a multiuser scenario. A framework was proposed for allocating the network resources energy efficiently.…”
Section: Backgroud and Preliminary Workmentioning
confidence: 99%
“…Energy harvesting (EH) is considered as one of the most robust methods to mitigate the energy consumption problem and perpetuate the lifetime and sustainability of wireless systems where around 30% of the energy expenditure of mobile devices is caused by wireless networking [4]. Radio frequency (RF) EH, which is also known as wireless energy transfer, has been introduced as an effective harvesting technique where energy is collected from RF sources generated by other neighbor devices.…”
Section: Introductionmentioning
confidence: 99%